P121Impaired autophagic flux in Mybpc3-targeted mice with cardiac hypertrophy. (15th July 2014) - Schlossarek, S; Singh, S; Geertz, B; Carrier, L
Abstract: Background:  The autophagy-lysosome pathway (ALP) is one of the major systems responsible for the degradation of cellular proteins and organelles. In cardiovascular diseases, activation or inhibition of this pathway has been described. However, there is not much known about alterations of the ALP in hypertrophic cardiomyopathy (HCM). Mutations in the MYBPC3 gene encoding cardiac myosin binding protein C (cMyBP-C) frequently cause HCM. In our previous study, elevated protein levels of autophagic markers, such as LC3 or p62, were obtained in Mybpc3-targeted knock-in (KI) and knock-out (KO) mice with HCM. However, these data did not allow distinguishing between impaired or activated ALP. We therefore investigated the autophagic flux in isolated neonatal cardiac myocytes and in vivo in KI, KO and wild-type (WT) mice. Methods:  KI mice carry a Mybpc3 point mutation and express low levels of mutant cMyBP-C, whereas KO mice do not express any cMyBP-C. KI, KO and WT mice of different postnatal ages (10, 30, and 57-week-old) were treated with 40 mg/kg ALP inhibitor leupeptin for 1 hour. Neonatal cardiac myocytes were treated with 10 μM ALP inhibitor chloroquine for 24 h. Autophagic flux was analyzed by Western blot detecting the turnover of cytosolic LC3-I to autophagosome membrane-bound LC3-II. Lysosomal function was assayed by cathepsin D protein level and activity. Autophagosome-lysosome fusion was indirectly measured by Rab7 protein level. Results:  Leupeptin treatment induced LC3-II accumulation in WT hearts, resulting in an increased LC3-II/LC3-I ratio. The increase in LC3-II/LC3-I ratio was less in KI than WT mice upon leupeptin treatment, suggesting ALP impairment in KI. The extent of impairment increased with age of the mice, being absent in neonatal cardiac myocytes, low in 10-, moderate in 30-, and severe in 57-week-old KI mice. Similar results were obtained in 57-week-old KO mice, excluding mutant cMyBP-C as a trigger. Protein level and activity of cathepsin D did not differ between groups, indicating intact lysosomal function. In contrast, Rab7 protein level was lower in KI and KO mice than in WT, suggesting a block in the fusion of autophagosomes and lysosomes. Conclusion:  These data provide evidence for an impaired autophagic flux that becomes more severe with age in HCM mice lacking functional cMyBP-C. This impairment results probably from a block in autophagosome-lysosome fusion rather than a lysosomal dysfunction.